Fiscal sustainability: an empirical investigation in Sarawak - Lau, Evan Poh Hock; Tiong, Magdalene Hua Ling; Ling, Jeffrey (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
This paper examines the fiscal sustainability condition for Sarawak during 1971 to 2004. We also split the sample period into the pre-crisis (1971-1996) to investigate the disparities between the two empirical samples. Empirical validation from the time series analysis finds that government revenue, government expenditure and Gross domestic Product (GDP) are cointegrated, which provides some support for the position that Sarawak’s budget deficit is sustainable in the long run in both sampling periods. The results also found support for coefficient of expenditure being unity in both periods. This finding suggests that reducing the size of government spending may improve fiscal budget deficits without having to undergo changes in the overall strategy.